Investigation of Sodium Silicate, Kaolinite, Cement and Water Effects' on Rheological and Physical Properties on Cement Based Grouts in Geotechnical and Geological Engineering - Sina Kazemian (Iranian Society of Structrual Engineering (ISSE), 2019)
Due to the growing population growth in cities, the use of injection technology in the ground improvements, construction industry, geotechnical and geological engineering is increasing day by day. In this regard, the grout and its additive play a very important role in terms of injection conditions. In this research, viscosity and rheological measurements of grout using the viscosimeter of the model (DV-II + Pro) as well as the physical criteria of the grout, including shrinkage, specific gravity (Gs), acidity (pH) on the cement base grout with the chemical additive like sodium silicate, kaolinite as mineral additive, cement and water were investigated. In this research, various grout compounds containing various percentages of sodium silicate, kaolinite and water were prepared. The results show that cement, kaolinite and sodium silicate have a reverse effect on the viscosity of the grout. If the amount of soil specific soil is acceptable and the soil acidity is more than 11, which is very suitable for injection operations. Also, the effect of various sodium silicate percentages on the binding properties, specific mass and gravity of acidity were investigated, and the results are recommended for geological and geotechnical engineers especially people who are working ans studying in this field.